Bidding for Firms with Unknown Characteristics - Johannes Becker; Andrea Schneider (Center for Economic Studies and ifo Institute (CESifo), 2014)
When a region successfully attracts a large firm by offering tax concessions, outright subsidies etc., the firm often commits itself to performance targets in terms of investment or employment. This paper interprets these contractually fixed targets as a consequence of incomplete information. It analyzes a model of two regions which compete for a large firm assuming that the firm's characteristics are ex-ante unknown. We consider direct mechanisms that induce truthful reporting of the firm's type as well as simpler bidding strategies. We find that, first, performance targets are an equilibrium outcome if information is incomplete. Second, these performance targets often induce employment distortions (overemployment in the most plausible case). Third, when the competing regions differ, the winning region may gain from the fact that information is incomplete, i.e. its payoff is greater than it would be under complete information. Finally, when the governments' sets of instruments are restricted to lump-sum payments, simple tax rebates and wage subsidies, incomplete information has no efficiency cost. This implies that restricting both regions' sets of policy instruments may improve efficiency.
Keywords: H25; H32; H87; 330; business taxation; state aids; subsidy competition; incomplete information; mechanism design